Rotational shear effects on edge harmonic oscillations in DIII-D quiescent H-mode discharges. (21st June 2016) - Chen, Xi; Burrell, K.H.; Ferraro, N.M.; Osborne, T.H.; Austin, M.E.; Garofalo, A.M.; Groebner, R.J.; Kramer, G.J.; Luhmann, N.C.; McKee, G.R.; Muscatello, C.M.; Nazikian, R.; et al.
Abstract: In the quiescent H-mode (QH-mode) regime, edge harmonic oscillations (EHOs) play an important role in avoiding transient edge localized mode (ELM) power fluxes by providing benign and continuous edge particle transport. A detailed theoretical, experimental and modeling comparison has been made of low- n ( n   ⩽  5) EHO in DIII-D QH-mode plasmas. The calculated linear eigenmode structure from the extended magentoohydrodynamics (MHD) code M3D-C1 matches closely the coherent EHO properties from external magnetics data and internal measurements using the ECE, BES, ECE-Imaging and microwave imaging reflectometer (MIR) diagnostics, as well as the kink/peeling mode properties found by the ideal MHD code ELITE. Numerical investigations indicate that the low- n EHO-like solutions from M3D-C1 are destabilized by rotation and/or rotational shear while high- n modes are stabilized. This effect is independent of the rotation direction, suggesting that EHOs can be destabilized in principle with rotation in either direction. The modeling results are consistent with observations of EHO, support the proposed theory of the EHO as a low- n kink/peeling mode destabilized by edge E  ×  B rotational shear, and improve our understanding and confidence in creating and sustaining QH-mode in present and future devices.